A study on use of wobble features in laser welding of low alloy steel joint with butt joint configuration - Kankala Timo; Salminen Antti (United Kingdom, 2022)
Laser welding is modern digital welding process, which thanks to several advantages over traditional welding processes, is gaining ever growing role in manufacturing. The process has still some weaknesses. The better the beam quality the smaller the focal point, the actual welding tool, diameter is. Typically, because of this the welding of joints with lesser quality e.g. larger air gap is difficult or even impossible. So-called beam manipulation opens opportunities to deal with the problem. The dynamic beam manipulation gives opportunities to control the weld dimensions during the welding process by the requirements of individual locations of weld joint. This study used the two dimensional scanner to manipulate beam during welding with so called wobble function. Four different wobble configurations were tested in welding of low-alloyed steel with different joint qualities. The wobble typically made the welds wider, provided typically higher heat input and thus lowered the hardness of the joint. Wobble increased typically the root quality, but there are differences between different wobble parameters. It was possible to weld joints with wider air gaps in the selected material thickness, but the wider air gap and wobble caused finally, when wide enough the sagging of the joint.
18th Nordic Laser Materials Processing Conference (18th NOLAMP) 18th-20th January 2022, Luleå, Sweden